Comparison of different types of phacoemulsification tips. I. Quantitative analysis of elemental composition and tip surface microroughness. Issue 9 (September 2016) - Tsaousis, Konstantinos T.; Werner, Liliana; Perez, Jesus Paulo; Li, He J.; Reiter, Nicholas; Guan, Jia J.; Mamalis, Nick
Abstract : Purpose : To evaluate the elemental composition of phacoemulsification tips and their surface roughness in the microscale. Setting : John A. Moran Eye Center and Utah Nanofab, College of Engineering, University of Utah, Salt Lake City, Utah, USA. Design : Experimental study. Methods : Seven types of phacoemulsification tips were studied. The phaco tips were examined through energy‐dispersive x‐ray spectroscopy (EDS) and x‐ray photoelectron spectroscopy (XPS) for elemental composition. In addition, the roughness of the opening in all tips was assessed through 3‐dimensional white‐light interferometry. Results : Elemental analysis showed considerable differences in the surface layers between manufacturers. Alcon tips had a thinner oxidized titanium (Ti) layer in their surface. Through XPS, vanadium was not detected in the superficial layers of any tip, but only in deeper levels. The microroughness surface analysis showed comparable results regarding their root‐mean‐square (RMS) metric. Maximum peak valley distance values varied and appeared to be dependent on the quality of material process rather than the material itself. Conclusions : Phacoemulsification tips are made of Ti alloys and showed differences between models, especially regarding their composition in the superficial layers. Their opening end roughness showed an overall appropriate RMS value of less than 1.0 μm in all cases. The existence of small defected areas highlights the importance of adequate quality control of these critical surgical instruments. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.